Kriteria al-GÄrimÄ«n sebagai Mustahik Zakat dalam Perspektif Fikih Islam - Ahmad Syaripudin; Hijrayanti Sari; Anita, Kurnaemi; Nur Sri Reski (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2021)
This research aimed to find out the specifications of al-gÄrimÄ«n referred to in the propositions on mustahik zakat and the perspective of Islamic jurisprudence on the criteria of al-gÄrimÄ«n entitled to zakat. This research was qualitative research with a normative juridical approach. The results of the study showed that al-gÄrimÄ«n belongs to one of the groups of people who are entitled to zakat or called mustahik of zakat. Scholars define it as a person who is in debt. There are gÄrim who owe for the benefit of themselves and their families, some who owe for the benefit of others such as reconciling two disputing groups. In the perspective of Islamic jurisprudency, gÄrim who are entitled to a share of zakat are those who meet the following criteria: Muslims; not ahlu bait; not a person who deliberately owes with the aim that gets a share of zakat; owed not in order to be maximal; the debt must be repaid immediately, not debt that is still pending to be repaid for several more years unless the debt must be repaid that year; has no savings to pay off his debts; owes to meet basic needs; not from muzakki dependents. The amount of zakat given to al-gÄrimÄ«n is as much as the debt that must be repaid.